Altered functional connectivity of the subthalamus and the bed nucleus of the stria terminalis in obsessive–compulsive disorder. Issue 6 (22nd August 2017) - Cano, M.; Alonso, P.; Martínez-Zalacaín, I.; Subirà, M.; Real, E.; Segalàs, C.; Pujol, J.; Cardoner, N.; Menchón, J. M.; Soriano-Mas, C.
Abstract : Background: The assessment of inter-regional functional connectivity (FC) has allowed for the description of the putative mechanism of action of treatments such as deep brain stimulation (DBS) of the nucleus accumbens in patients with obsessive–compulsive disorder (OCD). Nevertheless, the possible FC alterations of other clinically-effective DBS targets have not been explored. Here we evaluated the FC patterns of the subthalamic nucleus (STN) and the bed nucleus of the stria terminalis (BNST) in patients with OCD, as well as their association with symptom severity. Methods: Eighty-six patients with OCD and 104 healthy participants were recruited. A resting-state image was acquired for each participant and a seed-based analysis focused on our two regions of interest was performed using statistical parametric mapping software (SPM8). Between-group differences in FC patterns were assessed with two-sample t test models, while the association between symptom severity and FC patterns was assessed with multiple regression analyses. Results: In comparison with controls, patients with OCD showed: (1) increased FC between the left STN and the right pre-motor cortex, (2) decreased FC between the right STN and the lenticular nuclei, and (3) increased FC between the left BNST and the right frontopolar cortex. Multiple regression analyses revealed a negative association between clinical severity and FC between the right STN and lenticular nucleus. Conclusions: This study provides a neurobiological framework to understand the mechanism of action of DBS on the STN and the BNST, which seems to involve brain circuits related with motor response inhibition and anxiety control, respectively.